2011
DOI: 10.1002/ange.201100884
|View full text |Cite
|
Sign up to set email alerts
|

Tunable, Ultrasensitive pH‐Responsive Nanoparticles Targeting Specific Endocytic Organelles in Living Cells

Abstract: Umgebungseinfluss: Anpassbare, pH‐responsive Nanopartikel können selektiv in endozytischen Kompartimenten aktiviert werden. Bei hohen pH‐Werten bewirkt die Micellenbildung (links im Bild) eine Fluoreszenzlöschung durch Förster‐Energietransfer. Bei niedrigen pH‐Werten lösen sich die Micellen auf, was zu Fluoreszenz führt. Diese nichtlineare An/Aus‐Nanoplattform sollte für die diagnostische Bildgebung und den Wirkstofftransport interessant sein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 67 publications
1
56
0
2
Order By: Relevance
“…174 Another very interesting micelle-based sensor for measuring pH has been synthesized based on the selforganizing properties of the polymers, where the integrity of the micelle changes with pH, giving rise to a dequenching of the fluorophore signal that could then be monitored. 175,176 This principle was first reported by the authors in 2011 for probing early and late endosomes in cells and has later been shown to have interesting potential for in vivo detection of pH changes.…”
Section: Chemical Reviewsmentioning
confidence: 94%
“…174 Another very interesting micelle-based sensor for measuring pH has been synthesized based on the selforganizing properties of the polymers, where the integrity of the micelle changes with pH, giving rise to a dequenching of the fluorophore signal that could then be monitored. 175,176 This principle was first reported by the authors in 2011 for probing early and late endosomes in cells and has later been shown to have interesting potential for in vivo detection of pH changes.…”
Section: Chemical Reviewsmentioning
confidence: 94%
“…As stated above, the high trasfection activity of HBPO(OEI600-PBA) 10 was thought to associate with the weakened siRNA affity after the intracellular decomposition triggered by the remarkably lysosome acidity. [29] The western blot experiments further manifested the good transfection performance of HBPO(OEI600-PBA) 10 /Beclin1 siRNA in the transfected cells. In comparison, the negative control transfected with no-targeting NC-siRNA affected insignificantly the expression of Beclin 1 protein.…”
Section: In Vitro Beclin1 Sirna Transfectionmentioning
confidence: 96%
“…Ultrapure water was added to adjust the polymer concentration for experiment. The dispersion was filtered through a 0.22 mm filter before use [26,27].…”
Section: Preparation Of Copolymers Micellar Solutionmentioning
confidence: 99%